Nussbaum, Martha C. (2010). Sin fines de lucro. Por qué la democracia necesita de las humanidades. Buenos Aires: Katz Editores. ISBN Argentina: 978-987-1566-37-2. ISBN España: 978-84-92946-17-4. Número de páginas: 199. - Jiménez Bósquez, Diego (2011)
null